1989
DOI: 10.1212/wnl.39.8.1077
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent expression of neuronopathy after experimental pyridoxine intoxication

Abstract: We examined the sequence of nervous system abnormalities that resulted when rats were given excess amounts of vitamin B6 (pyridoxine). High doses of pyridoxine (1,200 or 600 mg/kg/d) for 6 to 10 days caused a neuronopathy with necrosis of dorsal root ganglion (DRG) sensory neurons, accompanied by centrifugal axonal atrophy and breakdown of peripheral and central sensory axons. Large diameter neurons with long processes and large cytoplasmic volumes were especially affected. Smaller doses (300 to 150 mg/kg/d) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 0 publications
1
46
0
1
Order By: Relevance
“…Pyridoxine is a toxin known to target large fiber sensory neurons (Albin et al, 1987); Krinke and Fitzgerald, 1988;Schaeppi and Krinke, 1982;Windebank et al, 1985;Xu et al, 1989). As such, we have previously demonstrated that pyridoxine intoxication causes a reduction in the mean area of A-and B-cells in the DRG .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Pyridoxine is a toxin known to target large fiber sensory neurons (Albin et al, 1987); Krinke and Fitzgerald, 1988;Schaeppi and Krinke, 1982;Windebank et al, 1985;Xu et al, 1989). As such, we have previously demonstrated that pyridoxine intoxication causes a reduction in the mean area of A-and B-cells in the DRG .…”
Section: Discussionmentioning
confidence: 93%
“…The rationale for selecting pyridoxine to produce an animal model of large-fiber neuropathy is based on several factors, including the selective and severe neurotoxic actions of this compound on large DRG neurons in rodents (Xu et al, 1989), dogs (Schaeppi and Krinke, 1982), and humans (Albin et al 1987). Our interest in this particular animal model of sensory neuropathy is that the rapidly developing, large fiber neurodegeneration may be considered to model one aspect of clinical diabetic peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower, more prolonged doses caused sublethal neuronal injury, with associated nerve fiber degeneration that was more profound distally (62). Another pattern of evolution of pyridoxine-induced neuropathy was somatofugal axonal atrophy with modest axonal degeneration (112). One study indicates that there is relatively uniform fiber degeneration along the entire length of the nerve with oral doses of 300 mg/kg for 8 or more days in dogs (60 (24), and the family of pyrimidines is known to have structurally dependent neurotoxic potential (93).…”
Section: Pyridoxine Neurotoxicitymentioning
confidence: 99%
“…Nous presentons le cas d'un homme de 18 ans traite de facon chronique depuis sa naissance par des doses elevees de pyridoxine (vitamine B 6 ), jusqu'a 2000 mg par jour, pour une epilepsie resistante a la pyridoxine. En moins de deux ans du debut du traitement, il a developpe une neuropathie sensitive qui n'a pas progresse pendant les 16 annees suivantes.…”
unclassified